Factors Influencing Undergraduate Students’ Motivation for Junk Food (OCEM Journal of Management, Technology & Social Sciences, 2024)
Consuming junk food is linked to several health problems, including obesity, diabetes, heart disease and cancer. The objective of this study was to examine the undergraduate students’ motivation for junk food. This study applied a quantitative research design to examine undergraduate students’ motivation towards junk food choices and the resulting contentment. A survey instrument was employed to collect comprehensive data on factors influencing student’s motivation, using a descriptive statistical analysis method. A representative sample of two hundred participants was selected through a simple random sampling technique. The results of this research indicate a positive association between prioritizing healthy and quality food and convenience food that tends to challenge a healthy diet and undergraduate students’ motivation for junk foods. The results further show a negative association between guardians’ influence, easy access to junk food, college regulations, attractive adds, health impact, the decision to buy junk food and motivation of undergraduate students on junk foods. The implications of this study would benefit policymakers, researchers, academicians, college leaders, teachers and faculty members of educational institutions to understand the current trends of undergraduate student on junk food consumption. Furthermore, the results add new literature on the motivation of junk foods among undergraduate students in the Neplese context. Future research is expected to examine the influencing factors to consume junk food in detail and large scale research.